Impact of Corporate Social Responsibility on Customer Loyalty and the Mediating Role of Affective Identification - B., Saju; Rajan, Kalyani Ranga (Indian Journal of Marketing, 2014)
This paper investigates the impact of perceived corporate social responsibility on customer loyalty with a model incorporating perceived product attributes and consumers' affective identification with a company. Using a survey with the customers of an ethnic apparel retailer brand, this study established that CSR has a significant impact on customer loyalty, and this process is mediated by consumers' affective identification with the company as a result of CSR. This study extended the extant literature by testing and validating the role of perceived CSR and affective identification on loyalty formation in the Indian context. It was also observed that CSR has a better scope to bring about affective ties with a company than conventional product attributes. The research suggested that marketers need to create engagement platforms with customers to create strong points of differentiation based on CSR, when consumers perceive parity on product attributes between competing offerings.